2015
DOI: 10.1016/j.stemcr.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Stable X Chromosome Reactivation in Female Human Induced Pluripotent Stem Cells

Abstract: SummaryIn placental mammals, balanced expression of X-linked genes is accomplished by X chromosome inactivation (XCI) in female cells. In humans, random XCI is initiated early during embryonic development. To investigate whether reprogramming of female human fibroblasts into induced pluripotent stem cells (iPSCs) leads to reactivation of the inactive X chromosome (Xi), we have generated iPSC lines from fibroblasts heterozygous for large X-chromosomal deletions. These fibroblasts show completely skewed XCI of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…However, one of the genes described in our analysis, GYG2 , has been shown to reactivate during early iPSC reprograming [59]. Recent reports also show that Xi genes that are reactivated at early iPSC stages can undergo subsequent de novo inactivation, probably due to inappropriate culture conditions [59, 60]. Interestingly, some genes that have been shown to be reactivated at late iPSC stages, including PDHA1 and IDS , are reactivated by cell fusion-mediated reprograming after 5azaC pre-treatment of somatic clones.…”
Section: Discussionmentioning
confidence: 95%
“…However, one of the genes described in our analysis, GYG2 , has been shown to reactivate during early iPSC reprograming [59]. Recent reports also show that Xi genes that are reactivated at early iPSC stages can undergo subsequent de novo inactivation, probably due to inappropriate culture conditions [59, 60]. Interestingly, some genes that have been shown to be reactivated at late iPSC stages, including PDHA1 and IDS , are reactivated by cell fusion-mediated reprograming after 5azaC pre-treatment of somatic clones.…”
Section: Discussionmentioning
confidence: 95%
“…The prevailing model therefore suggests that human primed female ESCs and iPSCs undergo XCI during differentiation, but the literature on the state of the X in undifferentiated PSCs and upon differentiation has remained controversial (Anguera et al, 2012; Barakat et al, 2015; Hall et al, 2008; Hoffman et al, 2005; Kim et al, 2014; Lengner et al, 2010; Mekhoubad et al, 2012; Nazor et al, 2012; Pomp et al, 2011; Shen et al, 2008; Silva et al, 2008; Tchieu et al, 2010; Tomoda et al, 2012; Vallot et al, 2015; Xie et al, 2016). We applied genomics approaches and multi-gene RNA FISH to define the XCI-state in ESCs at both the single cell and population level (summarized in Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of XCI in vivo , the X-chromosome state of human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) has been addressed by a number of researchers, arriving at the conclusion that these cells have different XCI-states (Anguera et al, 2012; Barakat et al, 2015; Hall et al, 2008; Hoffman et al, 2005; Kim et al, 2014; Lengner et al, 2010; Mekhoubad et al, 2012; Nazor et al, 2012; Pomp et al, 2011; Shen et al, 2008; Silva et al, 2008; Tchieu et al, 2010; Tomoda et al, 2012; Vallot et al, 2015; Xie et al, 2016). At least four X-chromosome states have been described: (i) two active X-chromosomes without XIST expression (XaXa); (ii) an XIST RNA-coated Xi with an Xa (Xi XIST + Xa); (iii) an Xi lacking XIST expression with an Xa (XiXa); and (iv) an Xi lacking XIST RNA with partial loss – erosion – of its silent state (eroded Xi, Xe) with an Xa (XeXa).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple groups have reported that XCR takes place during human reprogramming as evidenced by reactivation of X-linked genes in human iPSC (hiPSC) lines [71,72,75]. By contrast, others, including our group, reported that female hiPSCs do not show reactivation of X-linked genes and retain an Xi [73,74,76].…”
Section: Xcr In Human Reprogramming and In Pluripotent Stem Cellsmentioning
confidence: 93%